Analisis Determinan Underpricing Saham pada Perusahaan yang Tercatat Melakukan IPO di IDX 2021-2023 - Mina Olivia Rahayu; Triyono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of current ratio, debt to equity ratio, return on assets, earnings per share, underwriter,and share offering percentage on stock underpricing during initial public offering (IPO) on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach, using secondary data. The population of this study includes all companies that conducted initial public offerings on the Indonesia Stock Exchange in 2021-2023. Research samples using purposive sampling. Data analysis using Logistic regression analysis. The results showed that the current ratio, earnings per share, underwriter, share offering percentage significantly affect the stock underpricing, while the variable debt to equity ratio, return on does not affect the stock underpricing